Wound Healing Effect of an in Situ Forming Hydrogel Loading Curcumin-Phospholipid Complex - Du, Lina; Feng, Xue; Xiang, Xiaoqin; Jin, Yiguang (Current Drug Delivery, 2016)
Wound is one of most commonly clinical diseases. Curcumin is known to improve wound healing but its bioavailability and therapeutic efficiency are very low. Here we firstly report the application of phospholipid complexes to wound healing. A curcumin-phospholipid complex (CPC) was prepared with a solvent-evaporation method. The X-ray diffraction showed that the CPC was amorphous, which was further demonstrated with the electron microscopy. Furthermore, the CPC was loaded into a poloxamer in situ forming hydrogel (ISG). The CPC ISG showed higher erosion rates than the curcumin ISG due to the amorphous structure of CPC, which could lead to increase in curcumin dissolution. The CPC ISG showed higher wound healing effect than the control on the rat skin wound model especially in the early phase. The epidermal recovery was highly improved by the CPC ISG compared to the control. The CPC ISG is a promising formulation as an effective wound healing dressing.
Keywords: Wound healing